Preliminary note on the morphological characters of penja (amphidromous goby postlarvae) in West Sulawesi and Gorontalo Bay. (November 2019) - Nurjirana,; Haris, A; Sahami, F M; Keith, P; Burhanuddin, A I
Abstract: Penja is the local name for the postlarvae of fish belonging to the Gobioidei, whose appearance at certain times is an amphidromous migration process from the sea to rivers. This group of fish is generally referred to as amphidromous gobies. This study aimed to reveal some facts related to the species diversity of penja based on morphological characteristics. The study was conducted from October 2017 to March 2019 in West Sulawesi and Gorontalo Bay, Indonesia. Amphidromous goby samples at the penja (postlarval) stage were obtained from fishermen's catches and from traditional markets in each location. The samples obtained were measured and described based on morphological differences. The total length of the sampled penja ranged from 18 mm to 58 mm. All penja were identified as belonging to one of two families, the Gobiidae and Eleotridae. Although the species obtained from the waters of West Sulawesi and Gorontalo Bay were similar, there were variations in species composition (relative abundance) based on observed morphology of penja postlarvae from these two locations.